Stage III disease of ovarian, tubal and peritoneal cancers can be accurately diagnosed with pre-operative CT. Japan Clinical Oncology Group Study JCOG0602. (25th August 2020) - Onda, Takashi; Tanaka, Yumiko Oishi; Kitai, Satomi; Manabe, Tomoko; Ishikawa, Mitsuya; Hasumi, Yoko; Miyamoto, Kenichi; Ogawa, Gakuto; Satoh, Toyomi; Saito, Toshiaki; Kasamatsu, Takahiro; Nakanishi, Toru; et al.
Abstract: Purpose: Computed tomography of the abdomen and pelvis is a useful imaging modality for identifying origin and extent of ovarian cancer before primary debulking surgery. However, the International Federation of Gynecology and Obstetrics staging for ovarian cancer is determined based on surgico-pathological findings. The purpose of this study is to determine whether computed tomography staging can be the surrogate for surgico-pathological International Federation of Gynecology and Obstetrics staging in advanced ovarian cancer undergoing neoadjuvant chemotherapy. Methods: Computed tomography staging was compared with surgico-pathological International Federation of Gynecology and Obstetrics staging in primary debulking surgery arm patients in a randomized controlled trial comparing primary debulking surgery and neoadjuvant chemotherapy (JCOG0602). The cancer of primary debulking surgery arm was identically diagnosed regarding the origin and extent with the cancer of neoadjuvant chemotherapy arm before accrual, using imaging studies (computed tomography and/or magnetic resonance imaging), cytological examination (ascites, pleural effusion or tumor contents fluid) and tumor marker (CA125 > 200 U/mL and CEA < 20 ng/mL). Institutional computed tomography staging was also compared with computed tomography staging by central review. Results: Among 149 primary debulking surgery arm patients, 147 patients who underwent primary debulking surgery immediately were analyzed. Positive predictive values and sensitivity of computed tomography staging for surgical stage III disease (extra-pelvic peritoneal disease and/or retroperitoneal lymph node metastasis) were 99%. Meanwhile, positive predictive values for the presence of small (≤2 cm) extra-pelvic peritoneal disease were low; <20% in omentum. Accuracy of institutional computed tomography staging was comparable with computed tomography staging by central review. Conclusions: Preoperative computed tomography staging in each institution can be the surrogate for surgico-pathological diagnosis in stage III disease of ovarian cancer patients undergoing neoadjuvant chemotherapy without diagnostic surgery, but reliability of diagnosis of stage IIIB disease is inadequate. Clinical trial registration: UMIN000000523(UMIN-CTR). Abstract : Preoperative computed tomography staging can be the surrogate for surgico-pathological diagnosis in stage III disease of ovarian cancer, but reliability of diagnosis of stage IIIB disease is inadequate.